Arthropod Community in Hybrid Hazelnut Plantings in the Midwestern United States. Issue 4 (3rd July 2022) - Chediack, Ariadna; Liesch, Patrick J; Shanovich, Hailey N; Aukema, Brian H
Abstract: There is a lack of knowledge of the arthropod communities in both wild hazelnut and cultivated hybrid hazelnut ecosystems in the Midwestern United States. Our goal was to characterize the composition of these arthropod communities in hazelnut plantings. We surveyed six experimental plantings of hazelnuts in Wisconsin and two in Minnesota during growing seasons, from May 2017 to August 2021. We used four methods to survey the arthropod community of these plantings: ad libitum survey of specimen observations and collection, dissection of hazelnut buds and nuts, cone traps placed on the ground, and beat sheet sampling of plants. We registered 116 different morphospecies of five classes and 83 families. Arthropods with known feeding habits were grouped into four guilds: 59 herbivores, 36 carnivores (predators, parasites, and parasitoids), 4 decomposers (detritivores and scavengers), and 4 omnivores. While we registered 12 herbivorous species that could potentially cause damage to hazelnuts, we directly observed nine of them feeding upon or damaging plant parts: Phytoptus avellanae s.l. Nalepa (Eriophyoidea: Phytoptidae), Curculio obtusus Blanchard and Strophosoma melanogrammum Förster (Coleoptera: Curculionidae), Popillia japonica Newman (Coleoptera: Scarabeidae), Parthenolecanium sp. (Hemiptera: Coccidae), Euschistus servus euschistoides Say (Hemiptera: Pentatomidae), aphids (Hemiptera: Aphididae), Acleris sp., and Choristoneura rosaceana Harris (Lepidoptera: Tortricidae). We also registered eight species of parasites or parasitoids that could offer biocontrol services in the cropping system. These findings provide a foundation for future targeted studies on potential pests and beneficial arthropods, as well as ecological interactions within the hybrid hazelnut ecosystem in the Midwest.